Potato farmers' preference for agricultural insurance in China: An investigation using the choice experimental method - Ze-ying HUANG; Alec ZUO; Jun-mao SUN; Yan-zhi GUO (Journal of Integrative Agriculture, 2020)
Potato insurance plays an important role in transferring agricultural risks to promote the potato staple strategy. Understanding farmers' real preferences for potato insurance attributes is important to improve the potato insurance. In this study, a choice experiment was designed with attributes such as peril, minimum compensation ratio for production loss, types of crops covered by insurance, annual premium per mu after subsidy, and complexity of claims procedures. We constructed a mixed logit model based on a questionnaire survey of 362 potato farmers' choices of insurance attributes from 24 villages in Dingxi City of Gansu Province using random sampling. The results show that: (1) farmers prefer agricultural insurance with widely perils including output price drop and input cost risk; (2) farmers who have suffered plant disease and insect and pest damage are willing to pay a high premium for the insurance with a high compensation ratio and several types of crops covered; full-time farmers and large-scale farmers preferred insurance products with low complexity of claims procedures. Therefore, new potato insurance design could be considered specifically for different farmer groups such as those who had previous disaster experiences, and large- or small-scale farm operations.